Expectant management of severe early-onset preeclampsia in a low- resource setting: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2021)
Background: Severe early-onset preeclampsia is associated with increased likelihood of maternal complications and poor perinatal outcomes, regardless of expectant management.Case presentation: A 17-year-old primigravida at 30 weeks' gestation presented to the obstetric ward with complaints of headaches and painless per vaginal bleeding for one day. Her blood pressure was 174/106 mmHg. She had proteinuria of 3+. The ultrasound revealed a 30-week single intrauterine pregnancy with a partial placenta previa. A diagnosis of severe early-onset preeclampsia was made. She was started on expectant management with antihypertensives, antenatal corticosteroids, and magnesium sulfate with close monitoring. She developed hemolysis, elevated liver enzymes, low platelet count (HELLP) syndrome after seven days and was delivered by cesarean section. Her clinical condition improved markedly after delivery.Conclusion: Expectant management of severe early-onset preeclampsia can safely prolong pregnancy in select cases, with potential neonatal benefits.